A REVIEW OF DRAINAGE MANAGEMENT AND SUSTAINABILITY OF EGYPTIAN HEAVY CLAY SOILS - HUSSEIN, MAGED H.; HUSSEIN, MAGED H. (IJRDO - Journal of Business Management, 2017)
Reclamation and cultivation of heavy clay soils in Egypt are increased last decades due to high demand for food production. They are very attractive for agricultural expansion in the North of the Nile valley due to their high capacity of water holding and high fertility. High water table, high salinity and low permeability affect the productivity of heavy clay soils. The land drainage is required to improve the productivity these soils. Improvement of soil properties, suitable drainage systems, suitable drainage design, accurate drainage installation and maintenance are required to have feasible drainage system with good performance. The purpose of this paper is to summarize past and present drainage management practices and future challenges and technology to sustainability the agricultural expansion in the heavy clay soils of northern part of the Nile Delta.